Factors Influencing Stock Prices in Commercial Banks of Nepal - Joshi, Surendra Prasad; Ghimire, Binod; Singh, Shinju (KMC Research Journal, 2023)
This study explores the factors that influence stock prices in commercial banking business in Nepal. Descriptive and causal-comparative research design and purposive sampling technique used in this research examine how critical financial variables affect market prices per share (MPPS), including book value per share, earnings per share, dividend per share, and price-earnings ratio. There is a statistically significant but relatively small positive correlation between book value per share. The results show that MPPS and earnings per share, dividend per share, and price-earnings ratio are significantly positively correlated. The model demonstrates its robustness in capturing stock price changes by accounting for around 86.1% of the variation in MPPS. These observations offer insightful recommendations for experts and investors involved in Nepal's commercial banking sector.